2000
DOI: 10.1103/physreve.62.5409
|View full text |Cite
|
Sign up to set email alerts
|

Size, flexibility, and scattering functions of semiflexible polyelectrolytes with excluded volume effects: Monte Carlo simulations and neutron scattering experiments

Abstract: We present a systematic Monte Carlo study of the scattering function S(q) of semiflexible polyelectrolytes at infinite dilution, in solutions with different concentrations of added salt. In the spirit of a theoretical description of polyelectrolytes in terms of the equivalent parameters, namely, persistence length and excluded volume interactions, we used a modified wormlike chain model, in which the monomers are represented by charged hard spheres placed at distance a. The electrostatic interactions are appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…It has been shown that neglecting the interactions strongly affects the determination of micellar structural parameters, in particular the persistence length l p . 30,37,48,82,93,220,221 In the past few years, such structural models have been developed by Pedersen and Schurtenberger and co-workers, based on theory originally developed for polymers, combined with the results of Monte Carlo simulations, which now allow a full interpretation of the scattering data from long semiflexible micelles. 48,[220][221][222][223][224] For a recent review on the application of Monte Carlo techniques to obtain parameterized scattering functions for wormlike micelle systems, with and without electrostatic interactions, see ref.…”
Section: Extracting Structural Information: Scattering Techniquesmentioning
confidence: 99%
“…It has been shown that neglecting the interactions strongly affects the determination of micellar structural parameters, in particular the persistence length l p . 30,37,48,82,93,220,221 In the past few years, such structural models have been developed by Pedersen and Schurtenberger and co-workers, based on theory originally developed for polymers, combined with the results of Monte Carlo simulations, which now allow a full interpretation of the scattering data from long semiflexible micelles. 48,[220][221][222][223][224] For a recent review on the application of Monte Carlo techniques to obtain parameterized scattering functions for wormlike micelle systems, with and without electrostatic interactions, see ref.…”
Section: Extracting Structural Information: Scattering Techniquesmentioning
confidence: 99%
“…Structure factors are calculated differently for the entire simulation box representing an "infinite" system, and finite subsets. By treating the entire simulation box as the unit cell of an infinite cubic lattice, finite-size effects are avoided: the structure factor of the "infinite" system can be calculated at the reciprocal lattice points of the box, i.e., at certain q-values qp defined below, and in certain directions compatible with the cubic lattice: [51][52][53][54][55]…”
Section: Determination Of Small-angle Scatteringmentioning
confidence: 99%
“…Understanding the relationship between polyelectrolyte conformations, charged group distribution along the polymer backbone, and ionic strength is a complex problem that has been studied experimentally, theoretically, and in computer simulations. 3,[5][6][7][8][9][10][11][12][13][14] One of the most common measures of polyelectrolyte chain conformation is the persistence length. Persistence length impacts a wide range of polymer properties, such as intrinsic viscosity, 15 electrical conductivity, 16 and in concentrated solutions or in the bulk, ion clustering.…”
Section: Introductionmentioning
confidence: 99%